CROT (Carnitine O-Octanoyltransferase) Is a Novel Contributing Factor in Vascular Calcification via Promoting Fatty Acid Metabolism and Mitochondrial Dysfunction. Issue 2 (February 2021) - Okui, Takehito; Iwashita, Masaya; Rogers, Maximillian A.; Halu, Arda; Atkins, Samantha K.; Kuraoka, Shiori; Abdelhamid, Ilyes; Higashi, Hideyuki; Ramsaroop, Ashisha; Aikawa, Masanori; Singh, Sasha A.; Aikawa, Elena
Abstract : Objective: Vascular calcification is a critical pathology associated with increased cardiovascular event risk, but there are no Food and Drug Administration-approved anticalcific therapies. We hypothesized and validated that an unbiased screening approach would identify novel mediators of human vascular calcification. Approach and Results: We performed an unbiased quantitative proteomics and pathway network analysis that identified increased CROT (carnitine O-octanoyltransferase) in calcifying primary human coronary artery smooth muscle cells (SMCs). Additionally, human carotid artery atherosclerotic plaques contained increased immunoreactive CROT near calcified regions. CROT siRNA reduced fibrocalcific response in calcifying SMCs. In agreement, histidine 327 to alanine point mutation inactivated human CROT fatty acid metabolism enzymatic activity and suppressed SMC calcification. CROT siRNA suppressed type 1 collagen secretion, and restored mitochondrial proteome alterations, and suppressed mitochondrial fragmentation in calcifying SMCs. Lipidomics analysis of SMCs incubated with CROT siRNA revealed increased eicosapentaenoic acid, a vascular calcification inhibitor. CRISPR/Cas9-mediated Crot deficiency in LDL (low-density lipoprotein) receptor-deficient mice reduced aortic and carotid artery calcification without altering bone density or liver and plasma cholesterol and triglyceride concentrations. Conclusions: CROT is a novel contributing factor in vascular calcification via promoting fatty acid metabolism and mitochondrial dysfunction, as such CROT inhibition has strong potential as an antifibrocalcific therapy. Abstract : Supplemental Digital Content is available in the text.